Composición florística de la brioflora de la serranía del perijá (cesar-colombia): distribución y ecología (2001)
Richness and diversity of briophyte species from severallocalites in tropical and Subandean regions at Serrania del Perijá (Cesar- Colombia) were studied. All registers: of mosses (111 species) and thirteen of seventy - six hepatics are new corological novelties. Species established in the tropical region represent 5% ofthe total of species : meantime atthe Subandean zone occurs mostly ofthe species (95%).